Comparative Neurobiology of Biogenic Amines in Animal Models in Deuterostomes - D’Aniello, Enrico; Paganos, Periklis; Anishchenko, Evgeniya; D’Aniello, Salvatore; Arnone, Maria Ina (Frontiers in Ecology and Evolution, 2020)
We review the occurrence of biogenic amines and their potential role as neurotransmitters in the nervous system of three groups of invertebrate deuterostomes: tunicates, cephalochordates, and echinoderms. In addition to an overview of biogenic amines in each subphylum, we focus on a few species, including the sea squirts Ciona intestinalis, C. robusta, C. savignyi, and Phallusia mammillata (tunicates), the lancelets Branchiostoma lanceolatum and Branchiostoma floridae (cephalochordates), and the sea urchin Strongylocentrotus purpuratus (echinoderms). We chose these species as they are the most studied invertebrate deuterostomes in the field of evolutionary developmental biology (EvoDevo). Providing a comparative picture of the expression and role of neurotransmitters in deuterostomes will contribute to understanding the evolution of these neural signaling systems. Such an approach represents a new frontier of comparative neuroanatomy and neurobiology, and a prerequisite to uncover the homology of neuronal structures and circuits in deuterostomes with such diverse body plan organization and complexity.